2004
DOI: 10.1093/nar/gkh970
|View full text |Cite
|
Sign up to set email alerts
|

Thermoadaptation trait revealed by the genome sequence of thermophilic Geobacillus kaustophilus

Abstract: We present herein the first complete genome sequence of a thermophilic Bacillus-related species, Geobacillus kaustophilus HTA426, which is composed of a 3.54 Mb chromosome and a 47.9 kb plasmid, along with a comparative analysis with five other mesophilic bacillar genomes. Upon orthologous grouping of the six bacillar sequenced genomes, it was found that 1257 common orthologous groups composed of 1308 genes (37%) are shared by all the bacilli, whereas 839 genes (24%) in the G.kaustophilus genome were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(174 citation statements)
references
References 46 publications
1
172
1
Order By: Relevance
“…The genome of G. thermodenitrificans NG80-2 is composed of a 3,550,319-bp chromosome and a 57,693-bp plasmid, designated pLW1071, with mean G ϩ C contents of 49.0% and 39.8%, respectively (Table 1). Both the size and structure of the NG80-2 genome are similar to that of G. kaustophilus HTA426, the only other sequenced Geobacillus genome, which contains a 3,544,776-bp chromosome and a 47,890-bp plasmid (4). There are 3,499 predicted ORFs, 11 rRNA operons and 87 tRNA genes for all 20 aa, covering 86% of the genome (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The genome of G. thermodenitrificans NG80-2 is composed of a 3,550,319-bp chromosome and a 57,693-bp plasmid, designated pLW1071, with mean G ϩ C contents of 49.0% and 39.8%, respectively (Table 1). Both the size and structure of the NG80-2 genome are similar to that of G. kaustophilus HTA426, the only other sequenced Geobacillus genome, which contains a 3,544,776-bp chromosome and a 47,890-bp plasmid (4). There are 3,499 predicted ORFs, 11 rRNA operons and 87 tRNA genes for all 20 aa, covering 86% of the genome (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Polyamines such as norspermine and norspermidine are commonly found in hyperthermophilic bacteria and are necessary for the hyperthermophilic phenotype of those bacteria (27). Spermine is the major type of polyamine in Geobacillus species, and has been implicated in thermophily in G. kaustophilus based on the presence of the ''unique'' genes encoding spermine/spermidine synthase and polyamine ABC transporters (4). Those unique genes were also found in NG80-2 (GT1637, GT0623-GT0626).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic DNA of Geobacillus kaustophilus and Burkholderia xenovorans (formerly known as Burkholderia fungorum) were generous gifts from Hideto Takami (Japan Agency for Marine-Earth Science and Technology, Kanagawa, Japan) (18). The genomic DNA clone KNL023_G20 in the pTS1 plasmid containing the Nocardia farcinica icmF gene was obtained from Jun Ishikawa (National Institute of Infectious Diseases, Tokyo, Japan) (19).…”
Section: Cloning and Expression Of Icmfmentioning
confidence: 99%
“…HutP also exists in five other Bacillus species, including B. anthracis [23], B. cereus [24], B. halodurans [25], B. thuringiensis [26] and Geobacillus kautophilus [27] with 60% sequence identity. Sequence comparisons with the other Bacillus HutPs revealed that the C-terminal amino acid residues are more conserved than the N-terminal residues.…”
Section: Description Of the Hutpmentioning
confidence: 99%